“Join us to turn the world greener!“ – Investigating online apprenticeship advertisements’ reference to environmental sustainability - Binnewitt, Johanna [Verfasser]; Schnepf, Timo [Verfasser] (My University, 2023)
„The attractiveness of job ads positively influences job pursuit intentions of job seekers. With regards to an expected increasing labour shortage in the Green Economy, the question arises how attractively green apprenticeship job ads are promoted. Therefore, this exploratory study examines how strong job advertisement texts refer to environmental sustainability (ES). Based on 1.1 million German job ads for apprenticeships from 2011 to 2019 and a newly developed wordlist with 1,799 ES related expressions, we identify which advertisements refer to ES and with which strength they do so. Concerning strong signal words, we find a positive trend among those job ads that already contain ES related words such as “solar system” or “electro mobility”. (authors‘ abstract; BIBB-Doku)

„Die Attraktivität von Stellenanzeigen hat einen positiven Einfluss auf die Absicht von Arbeitssuchenden, sich auf eine Stelle zu bewerben. Im Beitrag wird untersucht, wie attraktiv Stellenanzeigen für „grüne“ Ausbildungsplätze beworben werden. Dafür untersuchen wir explorativ, wie stark sich Texte von Stellenanzeigen auf ökologische Nachhaltigkeit (ÖN) beziehen. Basierend auf 1,1 Millionen Stellenanzeigen für Ausbildungsplätze aus den Jahren 2011 bis 2019 und einer neu entwickelten Wortliste mit 1.799 ÖN-bezogenen Schlagwörtern, identifizieren wir, welche Anzeigen auf ÖN verweisen und mit welcher Stärke sie dies tun. In Bezug auf starke Signalwörter finden wir einen positiven Trend bei den Stellenanzeigen, welche bereits Technologien wie „Solaranlage“ oder „Elektromobilität“ benennen.“ (Autorenreferat; BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 6.4.8.1 Umweltberufe; 370; Ausbildungsplatz; Stellenanzeige; Analyse; Attraktivität; Umweltberuf; Nachhaltige Entwicklung